IMPLEMENTATION OF THE SMART SCHOOL APPLICATION WEB-BASED USING A PROTOTYPE MODEL - Haerani, Reni; Adi Nugroho, Praditya; Sofan Ansor, Ahmad (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2023)
Abstract: The advances in information technology have substantially affected the world of education. One of these impacts is the emergence of the concept of innovative schools. The Smart School application is a solution to increase the effectiveness and efficiency of managing the educational procedures in schools. This research intends to design a Smart School application using the Web-based Prototype method. The prototype method allows developers to design and develop application prototypes that can be tested by users (teachers, students, and parents) before implementing the actual application. This will help identify user needs, collect feedback and ensure that the resulting Smart School application meets the expectations and needs of all stakeholders. The Smart School application has many features, such as student data management, lesson schedules, homework and test management, communication between teachers, students and parents, and tracking student learning progress. This application is designed with a web interface like computers, tablets and smartphones. The resulting Smart School application using the Prototype approach will be better able to meet changing user needs and help improve the quality of education in schools. Apart from that, web technology will make it easier to access and use applications by all stakeholders in the world of education. Keywords: Smart School Application; Prototype; Website Abstrak: Kemajuan teknologi informasi sudah meninggalkan efek yang substansial terhadap dunia pendidikan. Salah satu dampak tersebut adalah munculnya konsep sekolah cerdas. Aplikasi Smart School merupakan solusi untuk meningkatkan efektivitas dan efisiensi pengelolaan prosedur pendidikan di sekolah. Riset ini bermaksud untuk merancang aplikasi Smart School dengan menggunakan metode Prototype berbasis Web. Metode Prototipe memungkinkan pengembang merancang dan mengembangkan prototipe aplikasi yang dapat diuji oleh pengguna (guru, siswa, dan orang tua) sebelum menerapkan aplikasi sebenarnya. Hal ini akan membantu mengidentifikasi kebutuhan pengguna, mengumpulkan umpan balik dan memastikan bahwa aplikasi Smart School yang dihasilkan memenuhi harapan dan kebutuhan seluruh pemangku kepentingan. Aplikasi Smart School dirancang dengan banyak fitur yang beragam seperti pengelolaan data siswa, jadwal pelajaran, pengelolaan pekerjaan rumah dan ulangan, komunikasi antara guru, siswa dan orangtua, serta pelacakan kemajuan perkembangan pembelajaran siswa. Aplikasi ini dirancang dengan antarmuka web seperti komputer, tablet, dan smartphone. Dengan menggunakan pendekatan Prototype, diharapkan aplikasi Smart School yang dihasilkan akan lebih mampu memenuhi perubahan kebutuhan pengguna dan dapat membantu meningkatkan kualitas pendidikan di sekolah. Selain itu, pemanfaatan teknologi web akan memudahkan akses dan penggunaan aplikasi oleh seluruh pemangku kepentingan di dunia pendidikan.Kata kunci: Aplikasi Smart School; Prototype; Website